Physicians and communities knowledge and awareness about new vaccines in immunization program: A study to derive lesson for increasing uptake - Lahariya, C; Khandekar, J; Vachher, AS; Pradhan, SK (Kathmandu University Medical Journal, 2010)
Background: The knowledge, attitude of physicians about any interventions has effect on the practices while the perceptions about such intervention by caregivers have impact on the acceptance in community. Objectives: This study was conducted to assess the knowledge and attitude of physicians and perception of the caregivers about new vaccines, and to identify the solutions to address the knowledge gap, if any. Materials and methods: A cross sectional study was conducted a major city of India from Sept 2006-Jan 2007. 107 physicians and 298 caregivers were interviewed using a pre-tested semi structured interview schedule. The data so collected was analyzed using chi square test and proportions. P value of less than 0.05 was considered statistically significant. Results: It was found that only 3/5th physicians were aware that typhoid vaccination was part of the immunisation program. The knowledge about all the aspects of typhoid was poor amongst physicians in comparison of other vaccine (Hepatitis B) in the immunisation program. Physicians at private health facilities had poor knowledge than those working at government health facilities. However, majority of the physicians had positive attitude towards typhoid vaccination. All the caregivers had heard about typhoid disease and 39.8% about the vaccine also. Almost 80% of them were ready to pay for typhoid vaccination. Conclusions: The study underlines the need for special efforts to increase the awareness about typhoid vaccination amongst these groups to increase the uptake of the vaccine. Key words: Child Health; Hepatitis B, India; Newer vaccines; Typhoid DOI: 10.3126/kumj.v8i1.3222 Kathmandu University Medical Journal (2010), Vol. 8, No. 1, Issue 29, 51-56